Patients and Holy Communion in danger death legislation synodal Polish pre-partition - GRĘŹLIKOWSKI, JANUSZ (Prawo Kanoniczne, 2017)
The issue of Holy Communion to the sick in legislation synodal Polish pre-partition is an interesting and important element of religious life and pastoral life of the Church that period. Resolutions of the synodal provide rich material defining and regulating the area of the sacramental life and religious believers. Lawmakers Synod be making and offering a number of provisions regarding the teaching and preparation of the faithful to the Eucharistic life, an important and worthy of granting and reception of the Eucharist, took care of it, took it to the faithful who are sick and in danger of death. They pointed to the difficulties and problems related to the life of the Eucharist and the reception of Holy Communion, which was to shape the life and attitude of the Christian and be secured to depart from this world. Requirements Eucharistic life find often the lack of good will and acceptance so of the faithful and pastors. Thus, the legislator Synod had direct words of rebuke and appropriate disciplinary and criminal orders. Christians proclaim in Poland distinguished Although sincere and spontaneous religiosity but in complying with the requirements of the Church as a Eucharistic life, sometimes showed a lot of tardiness and neglect. Resolutions and orders synods held in pre-partition Poland strongly influenced the religious life in Poland, including the right understanding and approach to adopt in distributing the Eucharist, the faithful sick. You could say that the legislation Synod Polish period pre-partition there were effectively the needs of the Polish Church in the religious life of the faithful and the Eucharist.